- 90
- 2
Let U be universe under consideration, and let P(x) and Q(x) be predicate with free variable x. Find a useful denial for (∀x∈U)(P(x)⇒Q(x))
Then my answer is:
¬(∀x∈U)(P(x)⇒Q(x))
(∃x∈U)¬(P(x)⇒Q(x))
¬(P(x)⇒Q(x))
¬P∨Q
I'm unsure if I am on the write path when it comes to finding the useful denial, is this how to do it?
Thank you.
Then my answer is:
¬(∀x∈U)(P(x)⇒Q(x))
(∃x∈U)¬(P(x)⇒Q(x))
¬(P(x)⇒Q(x))
¬P∨Q
I'm unsure if I am on the write path when it comes to finding the useful denial, is this how to do it?
Thank you.